Enumeration of Viable Non-Culturable Vibrio cholerae Using Droplet Digital PCR Combined With Propidium Monoazide Treatment - Zhao, Shuo; Zhang, Jingyun; Li, Zhe; Han, Yu; Kan, Biao (Frontiers in Cellular and Infection Microbiology, 2021)
Abstract Many bacterial species, including Vibrio cholerae (the pathogen that causes cholera), enter a physiologically viable but non-culturable (VBNC) state at low temperature or in conditions of low nutrition; this is a survival strategy to resist environmental stress. Identification, detection, and differentiation of VBNC cells and nonviable cells are essential for both microbiological study and disease surveillance/control. Enumeration of VBNC cells requires an accurate method. Traditional counting methods do not allow quantification of VBNC cells because they are not culturable. Morphology-based counting cannot distinguish between live and dead cells. A bacterial cell possesses one copy of the chromosome. Hence, counting single-copy genes on the chromosome is a suitable approach to count bacterial cells. In this study, we developed quantitative PCR-based methods, including real-time quantitative PCR (qPCR) and droplet digital PCR (ddPCR), to enumerate VBNC V. cholerae cells by counting the numbers of single-copy genes in samples during VBNC-state development. Propidium monoazide (PMA) treatment was incorporated to distinguish dead cells from viable cells. Both PCR methods could be used to quantify the number of DNA copies/mL and determine the proportion of dead cells (when PMA was used). The methods produced comparable counts using three single-copy genes (VC1376, thyA, and recA). However, ddPCR showed greater accuracy and sensitivity than qPCR. ddPCR also allows direct counting without the need to establish a standard curve. Our study develops a PMA-ddPCR method as a new tool to quantify VBNC cells of V. cholerae. The method can be extended to other bacterial species.